Electrochemical organic reactions: A tutorial review - Lodh, Joyeeta; Paul, Shounik; Sun, He; Song, Luyang; Schöfberger, Wolfgang; Roy, Soumyajit (Frontiers in Chemistry, 2023)
Electrochemistry, even though at its core involves simple oxidation and reduction reaction, can get intimidating for a chemist. The principles used in electrochemical reactions have been derived using physical organic chemistry, which drives any other organic/inorganic reactions. In this review, we have divided our article in two themes majorly. The first one discusses the factors that help with optimizing an electrochemical reaction which includes electrodes, supporting electrolytes, electrochemical cell design. The second half of the article outlines studies done in the field over a period of 10 years. The electrochemical reactions can be used as a versatile tool for synthetically important reactions just by modifying constant electrolysis current.